Surface integrity of SLM manufactured meso-size gears in laser shock peening without coating. (6th January 2023) - Pathak, Sunil; Böhm, Marek; Kaufman, Jan; Kopeček, Jaromír; Zulić, Sanin; Stránský, Ondřej; Shukla, Ashish; Brajer, Jan; Beránek, Libor; Radhakrisnan, J.; Rostohar, Danijela; Mocek, Tomáš
Abstract: The present work aimed to improve the surface integrity of the selective laser melting manufacturing (SLM) manufactured 10 mm sized meso gears using the unconventional Laser Peening without Coating (LPwC) technique. To accomplish LPwC on meso gears low energy in the range of 200 mJ to 1000 mJ at 10 Hz were applied underwater in the gear root and fillet gap generating significant surface compressive residual stresses (from +73 MPa to −298 MPa). Besides the surface, residual stresses, average surface roughness (Ra), arithmetical mean height (Sa) and parameters of the material ratio curve were also considered as a part of the study. Notable improvement was achieved in Sa, as it improved over 50 % while considerable improvement in Ra and the material ratio curve parameters has also been observed. Scanning electron microscopy confirmed that the void and porosity seen in the unpeened gears were filled. The electron backscatter diffraction analysis confirms the grain refinement in LPwC region up to 100 μm depth. It was observed that multifold dislocation occurs within the grain, and dislocation generates sub-grain. The sub-grain formation substantially inhibits further nucleation and crack propagation owing to an increase in grain boundary density. Such improvement justifies the set objectives, and the outcome of this research will pave a foundation to improve the overall performance of the micro/meso parts using the LPwC process.